Analisis Representasi Investasi Emas bagi Generasi Z di Media Sosial X: Antara FOMO, Risiko, dan Literasi Keuangan - Muhammad Zaki Fahrezi Alam; Ciek Julyati Hisyam; Muhammad Haichal Faresh; Jihandia Azzahra Ikna; Surya Hadi Muharam (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
Social media X significantly shapes Generation Z's investment behavior. This study analyzes how gold investment is represented on the platform by reviewing aspects of Fear of Missing Out (FOMO), risk perception, and financial literacy. A descriptive qualitative approach through content analysis was applied to various posts and discussions on X. The study findings show that social media X frames gold as a stable investment asset and a long-term store of value. FOMO drives impulsive investment actions among users. Financial literacy serves as a crucial factor in mitigating digital information distortions. Generation Z's investment decisions reflect rational actions influenced by digital social pressure and individual financial understanding.